Parallel Universes: The Infinite Number of Yous - Paudel, Lekhnath (International Research Journal of MMC, 2022)
Universe is everything that includes galaxies and stars as well as the source of energy. Universe is unimaginable, so we are able to experience different things. It is assumed that there are many universes like our universe. We cannot see and experience other universes due to its distance. Many researchers have been trying to prove the existence of parallel universes or multiverses. This study is done to explore about the knowledge of parallel universes or multiverses.Web search is conducted to explore and analyse the sources of information. Researcher hassearched relevant subject matters in 25 articles, which then were reviewed for its study area. Final list contained 13 articles. Then researcher reviewed the relevant subject matters necessary for the study from final list of articles. Many universes were initiated and existed many times in Big Bang. The existence of parallel universes will be beneficial for the endanger species like dinosaurs in case of natural calamities as an alternative universe to shelterfor existence.